Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd007396
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral opioids for maternal pain relief in labour

Abstract: Analysis 14.2. Comparison 14 IM tramadol versus no treatment, Outcome 2 Mean blood loss at delivery (ml).. . Analysis 15.1. Comparison 15 IM Avacan ® versus IM pentazocine, Outcome 1 Further analgesia required (nitrous oxide

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 19 publications
0
56
1
3
Order By: Relevance
“…1 Butorphanol, tramadol, nalbuphine, morphine, fentanyl, and remifentanil have also been used for labour analgesia; however, there is no clear evidence that any one drug is superior to any other. 2 Fentanyl and remifentanil are more popular for this indication as their pharmacokinetic and pharmacodynamic characteristics are favourable to meeting the intensity and undulating characteristics of labour pain.…”
Section: Résumémentioning
confidence: 99%
“…1 Butorphanol, tramadol, nalbuphine, morphine, fentanyl, and remifentanil have also been used for labour analgesia; however, there is no clear evidence that any one drug is superior to any other. 2 Fentanyl and remifentanil are more popular for this indication as their pharmacokinetic and pharmacodynamic characteristics are favourable to meeting the intensity and undulating characteristics of labour pain.…”
Section: Résumémentioning
confidence: 99%
“…The bio-medical model of care has resulted in the medicalisation of childbirth with increasing rates of epidural anaesthesia, particularly during normal labour (Walsh, 2012), embodying the pre-conceived assumption of pain implying suffering and requiring elimination (Simkin and Bolding, 2004). The administration of opioids during childbirth may offer some efficiency in pain relief, however, undesirable effects such as maternal nausea, drowsiness (Ullman et al, 2010) and potential compromise to the baby, causes concern about advocating their routine use (Heelbeck, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…No such risk has been described for meptazinol. The data comparing different parental opioids with respect to maternal satisfaction with therapy is generally unsatisfactory [17]. Our study showed that maternal satisfaction with pethidine therapy was comparable with satisfaction with meptazinol therapy in clinical practice.…”
mentioning
confidence: 53%
“…In the literature the analgesic effect of both opioids is usually classified as equivalent and as generally low, although sometimes meptazinol is judged to have a better side effects profile with less neonatal respiratory depression [15,16]. Very few studies have looked at maternal satisfaction with parenteral opioid therapy and, on investigation, the opioids are generally found to be comparable [17]. A comprehensive evaluation of pain management therapies should include the effects of therapy on maternal birth experience, as it does not necessarily depend on the extent of pain relief [18].…”
Section: Efficacy and Effects Of Parenteral Pethidine Or Meptazinol Amentioning
confidence: 99%